2021
DOI: 10.3390/ijerph18042139
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Health Professionals in the Management of Dysphagia

Abstract: The aim of this study was to determine healthcare providers’ knowledge and practices about dysphagia. A descriptive cross-sectional study was carried out based on a self-administered and anonymous questionnaire addressed to healthcare providers in Spain. A total of 396 healthcare providers participated in the study. Of these, 62.3% knew the definition of dysphagia as a swallowing disorder. In addition, up to 39.2% of the participants reported that they did not know whether the EatingAssessmentTool (EAT-10) dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…On the other hand, professionals have significant knowledge deficits in dysphagia management, and incorrect knowledge can be passed to patients. One study reported that 35.8% professionals did not know the definition of dysphagia as a swallowing disorder (Sánchez‐Sánchez et al, 2021). The lack of knowledge of healthcare professionals can lead to appropriate practices and increase the complications of dysphagia, which is an important barrier to the management of dysphagia patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, professionals have significant knowledge deficits in dysphagia management, and incorrect knowledge can be passed to patients. One study reported that 35.8% professionals did not know the definition of dysphagia as a swallowing disorder (Sánchez‐Sánchez et al, 2021). The lack of knowledge of healthcare professionals can lead to appropriate practices and increase the complications of dysphagia, which is an important barrier to the management of dysphagia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the prevalence of dysphagia is difficult to estimate and varies according to age, patient environment (out‐ or in‐patients), the assessment tool used for diagnosis and clinical expression (bronchitis, pneumonia, silent aspiration). The condition is mostly silent 10 and is mainly detected among elderly patients after hospital admission for concomitant conditions that can be either a cause or a consequence of dysphagia, 11 without it being the main cause of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of dysphagia experts and raters to rate FEES for diagnostic purposes has become a serious social problem 68 , 69 . The lack of timely diagnosis and treatment of dysphagia results in longer hospital lengths of stay, longer rehabilitation time, higher mortality, and higher healthcare expense 69 – 71 .…”
Section: Discussionmentioning
confidence: 99%